Pengaruh Kompensasi dan Motivasi Kerja Terhadap Peningkatan Kinerja Karyawan Pada PT. Triples Kediri - Divani, Amelia; Syahrinullah, Syahrinullah (Journal of Management Branding, 2024)
The effective utilisation of human resources is a fundamental aspect that plays a pivotal role in influencing the overall functioning of an organisation. PT Triples Kediri is a construction company with its headquarters located in Kediri City, Indonesia. Despite the company's overall success, there is considerable scope for improvement in the performance of its employees. This is attributable to the absence of adequate remuneration and incentives for employees. This research employs a quantitative methodology. This study employs both primary and secondary data sources. The data were collected through observation, documentation and questionnaires. The sample technique employed was purposive sampling, which yielded a total of 62 respondents. The test techniques employed include those for determining validity, reliability, classical assumptions, hypothesis testing and the coefficient of determination. The findings of this study indicate that the compensation variable exerts a partial influence on employee performance. Motivation variables exert a partial influence on employee performance. The simultaneous effect of compensation variables (X1) and motivation variables (X2) on the employee performance variable (Y) is 77.5%. The remaining 22.5% is influenced by variables outside the scope of this study